Study on the Construction of Wedge Functions for Degree n-Approximation over the Convex Quadrilateral Element - Rishabh Tiwari; P. L. Powar (Science and Technology - Recent Updates and Future Prospects Vol. 3, 2024)
In the present paper, we have focused our study on the construction, of wedge functions for degree n-approximation over the convex quadrilateral element. The construction of wedge functions over a quadrilateral element for linear approximation was reported by Wachspress. In particular, we have explored two different approaches to define the basis functions in accordance with the availability of data. In support of the construction, an illustrative example has been discussed. The study tried to develop the technique for higher degree approximation, which may be extended over any polygonal element of order m.